Anthropogenic noise compromises antipredator behaviour in European eels. (6th August 2014) - Simpson, Stephen D.; Purser, Julia; Radford, Andrew N.
Abstract Increases in noise‐generating human activities since the Industrial Revolution have changed the acoustic landscape of many terrestrial and aquatic ecosystems. Anthropogenic noise is now recognized as a major pollutant of international concern, and recent studies have demonstrated impacts on, for instance, hearing thresholds, communication, movement and foraging in a range of species. However, consequences for survival and reproductive success are difficult to ascertain. Using a series of laboratory‐based experiments and an open‐water test with the same methodology, we show that acoustic disturbance can compromise antipredator behaviour – which directly affects survival likelihood – and explore potential underlying mechanisms. Juvenile European eels (Anguilla anguilla) exposed to additional noise (playback of recordings of ships passing through harbours), rather than control conditions (playback of recordings from the same harbours without ships), performed less well in two simulated predation paradigms. Eels were 50% less likely and 25% slower to startle to an 'ambush predator' and were caught more than twice as quickly by a 'pursuit predator'. Furthermore, eels experiencing additional noise had diminished spatial performance and elevated ventilation and metabolic rates (indicators of stress) compared with control individuals. Our results suggest that acoustic disturbance could have important physiological and behavioural impacts on animals, compromising life‐or‐death responses.